2020
DOI: 10.3389/fimmu.2020.576818
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Diabetes in Patients Diagnosed With COVID-19

Abstract: COVID-19 is a disease caused by the coronavirus SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus-2), known as a highly contagious disease, currently affecting more than 200 countries worldwide. The main feature of SARS-CoV-2 that distinguishes it from other viruses is the speed of transmission combined with higher risk of mortality from acute respiratory distress syndrome (ARDS). People with diabetes mellitus (DM), severe obesity, cardiovascular disease, and hypertension are more likely to get infecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 123 publications
(124 reference statements)
3
73
0
4
Order By: Relevance
“…ACE2 is also found lining the cells of the pancreatic islets, hence patients with diabetes and hypertension can be treated with ACE inhibitors (ACEi) [ 38 ]. It has been established that SARs-CoV-2 enters the cell via the ACE2 receptor, hence the administration of ACEi to these patients can potentially exacerbate the progression of COVID-19 [ 23 ]. However, studies have shown that anti-hypertensive medications appear to have no impact on the prognosis of COVID-19 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ACE2 is also found lining the cells of the pancreatic islets, hence patients with diabetes and hypertension can be treated with ACE inhibitors (ACEi) [ 38 ]. It has been established that SARs-CoV-2 enters the cell via the ACE2 receptor, hence the administration of ACEi to these patients can potentially exacerbate the progression of COVID-19 [ 23 ]. However, studies have shown that anti-hypertensive medications appear to have no impact on the prognosis of COVID-19 [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that type 2 diabetes, which is the most prevalent type of the disease, is associated with low-grade chronic inflammation that affects the homeostatic glucose regulation and insulin sensitivity [ 23 , 24 ]. Studies have indicated that hyperglycemia may be a major pushing factor for a poorer prognosis of COVID-19, and has been a suggested risk factor for predicting ICU admission and negative outcomes in patients [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Almost immediately after the pandemic outbreak in China, greater vulnerability and higher incidence of severe clinical presentation and fatal outcome were observed in patients with particular preexisting conditions, especially in persons aged >65 1,2 . Numerous studies have shown that the greatest risk of severe COVID‐19 course/manifestation is posed by the presence of either diabetes mellitus, obesity, arterial hypertension, or immunosuppression / immunodeficiency 3‐8 . Severe COVID‐19 manifestations include development of extensive bilateral pneumonia, ARDS, and endothelial damage accompanied with accelerated thrombogenesis, which can all lead to the respiratory and multiorgan failure, being major clinical concern due to intensive care units overcrowding and high mortality rate 4,6 …”
Section: Discussionmentioning
confidence: 99%
“…Inappropriately excessive and uncontrolled inflammation more likely can result with the development of autodestrucitive cytokine storm, which is considered to be the final effector mechanism of tissue damage 4,6,10,11 . Obesity, insulin resistance and diabetes mellitus, as well as hypertension, are characterized by the presence of persistent low‐intensity inflammation, which may be decisive underlying factor amplifying and perpetuating viral‐induced inflammatory response 4‐11 . Some authors also suggest pathogenetic involvement of immunogenic damage‐associated molecular patterns (DAMPs), released as a consequence of preexisting disease 29 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation